Analysis of Tourism Business Regulations: Local Government Challenges in Implementing the Registration Policy - Hafied, Fadhliah; Alwi, Alwi (Jurnal Studi Ilmu Pemerintahan, 2024)
Tourism business regulation presents a governance challenge in districts where informal entertainment venues operate outside legal frameworks. In Sidenreng Rappang Regency, inconsistent enforcement of Ministry Regulation No. 18 of 2016 has enabled widespread non-compliance among nightlife businesses, compromising administrative credibility and social harmony. This study aims to assess the effectiveness of the registration policy implementation and identify institutional constraints affecting local governance capacity. Addressing a gap in region-specific policy diagnostics, the research applies a descriptive quantitative approach using structured questionnaires and interviews with 96 stakeholders, including business operators and officials. Pearson correlation analysis, supported by statistical validation using SPSS, indicates significant relationships between implementation outcomes and variables such as government seriousness (r = 0.261), assertiveness (r = 0.271), and registration accountability (r = 0.328). Enforcement efforts remain episodic, undermined by insufficient resources and limited procedural transparency. Stakeholders cite systemic weaknesses in administrative coordination and community engagement. The study concludes that effective regulation depends not only on formal mandates but also on contextual alignment between policy content and institutional behavior. Strengthening localized enforcement models, promoting inter-agency collaboration, and integrating public oversight are recommended to bridge the gap between law and practice. These insights may inform future frameworks for sustainable tourism governance in culturally sensitive regions.